D.H. Lawrence and survival : Darwinism in the fiction of the transitional period - Granofsky, Ronald, 1950- (McGill-Queen's University Press, 2003)
Although Darwin's ideas about evolution were dominant in D.H. Lawrence's day, little scholarly work has been done on the influence of these concepts on his work. In D.H. Lawrence and Survival Ronald Granofsky argues that Lawrence employed ideas based on evolution in his fiction, particularly during the transition between his "marriage" and "leadership" periods (1919-22) when he embarked on a major rethinking of the direction of his creative work, and that these ideas contributed to the deterioration in his fiction after Women in Love.